PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SD NEGERI 019 BUMI AYU KECAMATAN DUMAI SELATAN - Suswarni Suswarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The background of this study is the low learning outcomes of science subjects. Of 32 students, only 13 studentswhose learning outcomes are complete, the average student score is 57.78. Based on this is the researcher doingresearch by applying the model of learning based on the problem. This research was conducted at SD Negeri019 Bumi Ayu, with the subject of the study of the students of class VI with the number of students as many as 32students. The results stated that the application of inquiry learning model can increase the activity of teachersand students and the result of science learning. This is evidenced by: (1) teacher activity at meeting I cycle I getscore 20 (44,45%) at meeting II cycle I have increase with score 24 (54,55%). At the first meeting I cycle IIincreased with a score of 31 (75.22%), and at the second meeting II cycle increased with a score of 37 (84.09%).In addition, the students' activity increased during the first cycle meeting I got a score of 21 (47.73%), in thesecond meeting of cycle I increased by a score of 25 (56.82%). At the first meeting I cycle II increased with ascore of 35 (79.55%) and at the second meeting II cycle increased with a score of 37 (84.09%); and (2)improved student learning outcomes marked from 24 people on a baseline score to 16 in daily repeat I andincreased to 30 in daily repeat II.